Light-responsive hybrid material based on luminescent core-shell quantum dots and steroidal organogel - Schmidt, Luciana Carina (2016)
We report the synthesis of a smart novel hybrid with reversible photoswitchable luminescence properties modulated by light. The combination of a low molecular weight organogelator (LMOG) and CdSe/ZnS core-shell semiconductor nanoparticles capped with trioctylphosphine oxide ligands produces a luminescent, stable and transparent material. Modulation of the luminescence properties was successfully achieved using a diarylethene photochromic compound, with good resistance to fatigue ca. 22 cycles. Interestingly, the morphology of the organogel fibers was preserved in the hybrid, while a partial luminescence quenching of the nanoparticle was observed. This material could have implication for on-and-off photoswitching applications.